TASAWWUF mystical thought, practice and experience of selected Tausug practitioners - Ismael, Timhar H. (Institute of Islamic Studies, University of the Philippines Diliman, 2007)
This work is a study of the influence of Tasawwuf among Tausug.It focuses on Tausug mystical thought, practice and experience.